Weather data: a vital component to the agriculture value chain - Msengezi, Chipo; Nesoba, Dorah (Technical Centre for Agricultural and Rural Cooperation, 2018)
All agricultural stakeholders have an interest in accurate, localised and reliable meteorological data. Having access to such data means that organisations and entrepreneurs can translate raw weather data into accessible weather information, which is crucial for farmers to make well-informed farm management decisions and for effective risk mitigation.